2022
DOI: 10.1371/journal.pone.0266145
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of queen cell acceptance and royal jelly production between hygienic and non-hygienic honey bee (Apis mellifera) colonies

Abstract: Honey bees are crucial for pollination services globally and produce important hive products including honey, royal jelly, pollen, and propolis that are being used commercially in food, cosmetics, and alternative medicinal purposes. Among the bee products, royal jelly (RJ) has long attracted scientists’ interest because of its importance in honey caste differentiation. The present research was carried out to determine the acceptance rate of queen cells, and RJ production between the hygienic and non-hygienic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Therefore, one of the primary goals of royal jelly production operations is to increase the quality and quantity per colony via the creation of colony management systems. Numerous studies have shown the beneficial effects of honey and pollen substitute foods on the biology, brood growth, honey storage efficiency, comb construction, longevity, body weight, queen cell acceptance rate and queen cell weight of honey bee colonies (Herbert et al, 1977;Doull 1980;Winston et al, 1983;Dastouri and Maheri-Sis, 2007;Almaida-Dias et al, 2018;Adgaba et al, 2020;Oskay 2021;Khan and Ghramh 2022).…”
Section: -Hda Analysis Of Royal Jellymentioning
confidence: 99%
“…Therefore, one of the primary goals of royal jelly production operations is to increase the quality and quantity per colony via the creation of colony management systems. Numerous studies have shown the beneficial effects of honey and pollen substitute foods on the biology, brood growth, honey storage efficiency, comb construction, longevity, body weight, queen cell acceptance rate and queen cell weight of honey bee colonies (Herbert et al, 1977;Doull 1980;Winston et al, 1983;Dastouri and Maheri-Sis, 2007;Almaida-Dias et al, 2018;Adgaba et al, 2020;Oskay 2021;Khan and Ghramh 2022).…”
Section: -Hda Analysis Of Royal Jellymentioning
confidence: 99%
“…The PLOS ONE Editors retract this article [ 1 ] because it was identified as one of a series of submissions for which we have concerns about authorship, competing interests, and peer review. We regret that the issues were not addressed prior to the article’s publication.…”
mentioning
confidence: 99%